Differences in Physical Performance According to the Competitive Level in Amateur Handball Players. Issue 7 (July 2020) - Romaratezabala, Estibaliz; Nakamura, Fabio; Ramirez-Campillo, Rodrigo; Castillo, Daniel; Rodríguez-Negro, Josune; Yanci, Javier
Abstract : Abstract: Estibaliz, R, Fabio, N, Rodrigo, RC, Daniel, C, Josune, RN, and Javier Y. Differences in physical performance according to the competitive level in amateur handball players. J Strength Cond Res 34(7): 2048–2054, 2020—The aim of this study was to compare physical performance in amateur handball players of 2 different competitive levels. Thirty-four senior handball players were divided into 2 groups according to their competitive level (regional category: REG or national category: NAC). Although no significant differences were found between groups in any of the horizontal jump (HJ) or vertical jump (VJ) variables ( p > 0.05), NAC players obtained a better performance in the repeated sprint ability (RSA) test (RSABest [the best attempt] and RSATT [the total time in the total of sprints] in 15 m and 30 m), in change of direction ability (CODA) and in the Yo-Yo Intermittent Recovery Test Level 1 (YYIR1) test ( p < 0.01, effect size = −1.32 to 1.75, large). A significant association was observed between the body mass index (BMI) and the HJ or VJ capacity ( r = −0.35 to −0.55, p < 0.01), the RSA15mBest and RSA30mBest ( r = 0.41 to 0.59, p < 0.01), and YYIR1 distance ( r = −0.54, p ⩽ 0.05), and a also between the performance in the HJ or the VJ and the RSA15mBest and RSA30mBest, the CODA and the YYIR1, and between the RSA30mBest and the YYIR1 ( r = −0.54, p ⩽ 0.05). Specific strength and conditioning programs should aim toward improving RSA, CODA, and YYIR1, as these abilities may be needed at higher levels of competition. The programs also should aim toward improved HJ and VJ abilities, given their association with RSA, CODA, and YYIR1 performance. Moreover, maintaining an adequate BMI may aid players to sustain greater physical performance levels.